2015
DOI: 10.1186/s12864-015-1909-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the agrotis segetum pheromone gland transcriptome in the light of Sex pheromone biosynthesis

Abstract: BackgroundMoths rely heavily on pheromone communication for mate finding. The pheromone components of most moths are modified from the products of normal fatty acid metabolism by a set of tissue-specific enzymes. The turnip moth, Agrotis segetum uses a series of homologous fatty-alcohol acetate esters ((Z)-5-decenyl, (Z)-7-dodecenyl, and (Z)-9 tetradecenyl acetate) as its sex pheromone components. The ratio of the components differs between populations, making this species an interesting subject for studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 88 publications
7
36
0
Order By: Relevance
“…Herein, we identified a single PBANR in the S. insularis PG transcriptome that is 84% identical to Mamestra brassicae PBANR isoform B (ARO85772.1) and is very low in abundance (0.56 FPKM; Table 2 and S1 Text). The number of PBANR-encoding genes in the S. insularis PG was in accordance with Plutella xylostella [25], Agrotis segetum [58], and Agrotis ipsilon [59]. In addition, previous studies identified three isoforms of PBANR in Ostrinia nubilalis [60] and Mamestra brassicae [61].…”
Section: Pheromone Biosynthesis-activating Neuropeptide Receptor (Pbanr)supporting
confidence: 73%
“…Herein, we identified a single PBANR in the S. insularis PG transcriptome that is 84% identical to Mamestra brassicae PBANR isoform B (ARO85772.1) and is very low in abundance (0.56 FPKM; Table 2 and S1 Text). The number of PBANR-encoding genes in the S. insularis PG was in accordance with Plutella xylostella [25], Agrotis segetum [58], and Agrotis ipsilon [59]. In addition, previous studies identified three isoforms of PBANR in Ostrinia nubilalis [60] and Mamestra brassicae [61].…”
Section: Pheromone Biosynthesis-activating Neuropeptide Receptor (Pbanr)supporting
confidence: 73%
“…2). All three Mambr-PBANRs clustered with high bootstrap support with PBANR sequences from other noctuid species including Spodoptera littoralis (Zheng et al, 2007), H. virescens (Kim et al, 2008), S. exigua (Cheng et al, 2010), Pseudaletia separata, H. zea, H. armigera (Lee et al, 2012) and Agrotis segetum (Ding and Löfstedt, 2015). Furthermore, all of the receptors clustered in species specific clades.…”
Section: Cdna Cloningmentioning
confidence: 77%
“…Subsequent confirmation of this hypothesis facilitated homology-based identification of the PBANR in Helicoverpa zea (Choi et al, 2003) and Bombyx mori (Hull et al, 2004). Since then PBANRs have been identified in diverse moth (Cheng et al, 2010;Ding and Löfstedt, 2015;Kim et al, 2008;Lee et al, 2012;Nusawardani et al, 2013;Rafaeli et al, 2007;Zheng et al, 2007) with multiple PBANR isoforms (PBANR-As, -A, -B, and -C) shown to be concomitantly expressed in PGs (Kim et al, 2008;Lee et al, 2012). The isoforms are differentiated by the length and composition of their C-termini, which is necessary for the ligand-induced internalization (Hull et al, 2005), a phase of GPCR feedback regulation and desensitization (Moore et al, 2007;Marchese et al, 2008).…”
Section: Introductionmentioning
confidence: 90%
“…Although moth FARs usually exhibit a broad substrate preference [77,89,111,120,122,123], some of them display specificity to unsaturated substrates with a double bond in either the E or Z configuration [119], a particular chain length and double bond position [120], or a system of conjugated double bonds [118]. Given the multiple FAR paralogs generally present in insect genomes [13,14,16,17,111,124] and limited knowledge of their properties, there is a demand to perform functional characterization of these biologically and biotechnologically relevant enzymes. FARs from insects other than moths are virtually unexplored.…”
Section: Far Propertiesmentioning
confidence: 99%
“…The diversification of the pheromone-biosynthetic enzymes likely has been driven by evolutionarily imposed requirements on sex pheromone signal specificity [11,12]. A broad spectrum of insect pheromone-biosynthetic enzymes has already been functionally characterized, and transcriptomic sequencing (RNA-seq) of pheromone glands using next-generation sequencing has identified new candidates for characterization [13][14][15][16][17][18][19]. RNA-seq of other insect glands and tissues may open the door to the discovery of many additional enzymes with remarkable biosynthetic capabilities [8].…”
Section: Introductionmentioning
confidence: 99%